Perbaikan Teknologi Beternak Kambing di Desa Dhampulo Kabupaten Aceh Besar - Mawardi Mohd. Ali (Jurnal Agripet, 2001)
ABSTRACT A study on the correction of breeding goat technology in Dhampulo village was conducted from July 1996 to Desember 1997. Twenty Kacang goats divided into to groups. Each groub cossed with one FE male anf another groub crossed with Kacang Male. Reproduction and production performance of kid at both group was compared. The resilt of this study showed that group of PE male was better. Kid crop was 160 vs 120%, birth type was 60 vs 30%, birth weigt was 1.61 vs 1.33 kg and weight at one month age was 3.44 vs 2.72 kg.